Microstructural and Surface Plasmon Resonance Properties of Green-Synthesized Ag Nanoparticles Using Moringa oleifera Extract - Adrianto, Nanang; Istiqomah, Nurul Imani; Panre, Andi Marwanti; Suharyadi, Edi (Solid State Phenomena, 2022)
Ag nanoparticles (NPs) have been successfully synthesized by the green synthesis method using Moringaoleifera (MO) extract with various incubation times (24 and 48 hours) as an active material for surface plasmon resonance (SPR) biosensor. Transmission electron microscopy analysis indicated the formation of spherical particles with an average crystal size of 29 nm. Selected area electron diffraction confirmed that Ag NPs is face-centered cubic (FCC) crystal structure. Fourier-transform infrared measurements show the band at 3330 cm-1, 2067 cm-1, 1634 cm-1 for an incubation time of 24 hours and 3328 cm-1, 2063 cm-1, 1633 cm-1 for an incubation time of 48 hours. The results prove the proteins and phenolics compound present in the MO extract responsible as reducing agents. The maximum absorption of the green-synthesized Ag NPs in the UV-Vis spectra shows the SPR band at 326 nm and 328 nm for an incubation time of 24 and 48 hours, respectively, and absorption intensity decrease with the increase of incubation time. The result shows the SPR angle shifted to the larger angle of incident light by using green-synthesized Ag NPs. However, the increased incubation time affects the angle shift to the lower angle of the SPR shift. The addition of the green-synthesized Ag NPs leads to enhance the sensitivity of the SPR biosensor.